ExploriNg DUrable Remission with Rituximab in ANCA-associatEd vasculitis (ENDURRANCE trial): protocol for a randomised controlled trial. Issue 9 (21st September 2022) - Dirikgil, Ebru; van Leeuwen, Jolijn R; Dam, Laura S van; Bredewold, Obbo W; Ray, Argho; Jonker, Jacqueline T; Soonawala, Darius; Remmelts, Hilde H F; van Dam, Bastiaan; Bos, Willem Jan; van Kooten, Cees; Rotmans, Joris; et al.
Abstract : Introduction: Both rituximab (RTX) and cyclophosphamide (CYC) are effectively used in combination with steroids as remission induction therapy for patients with antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV). Several studies have shown that the effect on achieving (clinical) remission, frequency and severity of relapses is equivalent for both therapies, but there is accumulating data that the long-term safety profile of RTX might outperform CYC. Combination of RTX with low-dose CYC (LD-CYC) has been investigated in only a few uncontrolled cohort studies, in which clinical remission and a favourable immunological state with low relapse rates was quickly achieved. In this randomised controlled trial, we aim to investigate whether the combination treatment (RTX+LD CYC) is superior in comparison to standard care with RTX only. Methods and analysis: This study is an open-label, multicentre, 1:1 randomised, prospective study for patients with AAV with generalised disease, defined as involvement of major organs, that is, kidneys, lungs, heart and nervous system. In total, 100 patients will be randomised 1:1 to receive either remission induction therapy with standard of care (RTX) or combination treatment (RTX+LD CYC) in addition to steroids and both arms are followed by maintenance with RTX retreatments (tailored to B-cell and ANCA status). Our primary outcome is the number of retreatments needed to maintain clinical remission over 2 years. Secondary outcomes are relevant clinical endpoints, safety, quality of life and immunological responses. Ethics and dissemination: This study has received approval of the Medical Ethics Committee of the Leiden University Medical Center (P18.216, NL67515.058.18, date: 7 March 2019). The results of this trial (positive and negative) will be submitted for publication in relevant peer-reviewed publications and the key findings presented at national and international conferences. Trial registration number: NCT03942887 .